Indutores de resistência na proteção do cafeeiro contra a cercosporiose e na expressão de genes e proteínas de defesa - Guimarães, Sandra Eliza (2015)
The induction of resistance consists of the activation of plant defense mechanisms for the control of pests and diseases. Understanding the molecular phenomena involved in the pathogen and host interface, as well as the responses of plants to eliciting products, has demanded ever more studies. Gene and proteomic expressions have become important tools to obtain information regarding the mechanisms presented by the plants over a certain stress condition. The objective of this study was to analyze inducing products such as Acibenzolar S- Methyl (ASM) and the extract based on byproducts of the Greenforce Cuca coffee productive chain, on Coffea arabica seedlings, cultivar Mundo Novo 376/4, of which were verified the expression of defense enzymes lipoxygenase, catalase, glutathione peroxidase, by means of qRT-PCR, which were more expressive with the treatments, with ASM responding faster and Greenforce Cuca presenting slower, however more durable, effect. Another study was conducted to determine the protein profile of the plants treated with these products by means of two-dimensional electrophoresis and mass spectrometry. It was possible to verify the abundance of proteins related to photosynthetic processes and plant defense. We also noted that, in plants treated with ASM, there was a reduction in the abundance of proteins over the hours after applying this product and that the Greenforce Cuca presented a growing abundance over the hours after application for proteins related to defense and to photosynthetic processes. In general, the tested products presented inducing effect for plant resistance, evidenced by the results obtained.